Scientific substantiation of the essence of the principle of science in N.F. Sumtsov’s pedagogical heritage - Tatiana B. Kuzyoma (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the study of Sumtsov’s theoretical views on the principle of scientific teaching of students in schools and higher educational institutions. Leading ideas of understanding the scientific teaching of Russian and foreign scientists and philosophers in different historical periods are indicated. The main ways of implementing the scientific principle are described. The article presents the pedagogical views of N.F. Sumtsov on the science as a whole. The main requirements of the scientific principle concerning the content of education, the essence of scientific knowledge, the importance of the scientific outlook, the development of scientific knowledge of students are characterized. The main scientific requirements for professional and personal qualities of the teacher are determined. The ways of increasing the scientific professional growth of the teacher are considered. The role of scientific exhibitions and pedagogical congresses in raising the scientific level of teachers has been revealed.